Depression and somatization in patients with temporomandibular disorders in a population-based cross-sectional study in Southern Brazil - Rehm, Daniela D.S.; Progiante, Patrícia S.; Pattussi, Marcos P.; Pellizzer, Eduardo P. [UNESP]; Grossi, Patrícia K.; Grossi, Márcio L. (Quintessence Publishing, 2019)
Purpose: To assess the prevalence of depression and somatization in patients with temporomandibular disorders (TMD) in a Brazilian population-based cross-sectional survey. Materials and Methods: A total of 1,643 subjects were assessed for TMD using the Research Diagnostic Criteria for Temporomandibular Disorders Axes I and II and were assessed for depression and somatization using the Graded Chronic Pain Scale. The data were cross-tabulated for comparison between TMD subjects and controls. Results: TMD subjects had significantly worse depression and somatization levels than controls in the RDC/TMD Axis II. The levels were also worse in most Axis I TMD groups (muscle disorders and arthralgia/osteoarthritis/osteoarthrosis). Conclusion: TMD subjects had worse depression and somatization, particularly in diagnostic groups with higher pain/disability levels.